Thermally triggered injectable hydrogel, which induces mesenchymal stem cell differentiation to nucleus pulposus cells: Potential for regeneration of the intervertebral disc. (May 2016) - Thorpe, A.A.; Boyes, V.L.; Sammon, C.; Le Maitre, C.L.
Graphical abstract: In vitro differentiation of MSCs into NP-like cells, following incorporation into pNIPAM-DMAc-Laponite® hydrogel cultured under 5% O2 for 6 weeks with increased production of NP matrix and phenotypic markers. This hydrogel system has the potential to deliver MSCs via minimally invasive injection to regenerate the NP for the treatment of IVD degeneration, a major cause of low back pain. Abstract: There is an urgent need for new therapeutic options for low back pain, which target degeneration of the intervertebral disc (IVD). Here, we investigated a pNIPAM hydrogel system, which is liquid at 39 °C ex vivo, where following injection into the IVD, body temperature triggers gelation. The combined effects of hypoxia (5% O2 ) and the structural environment of the hydrogel delivery system on the differentiation of human mesenchymal stem cells (hMSCs), towards an NP cell phenotype was investigated. hMSCs were incorporated into the liquid hydrogel, the mixture solidified and cultured for up to 6 weeks under 21% O2 or 5% O2 where viability was maintained. Immunohistochemistry revealed significant increases in NP matrix components: aggrecan; collagen type II and chondroitin sulphate after culture for 1 week in 5% O2, accompanied by increased matrix staining for proteoglycans and collagen, observed histologically. NP markers HIF1α, PAX1 and FOXF1 were also significantly increased where hMSC were incorporated into hydrogels with accelerated expression observed when cultured in 5% O2 . hMSCs cultured under hypoxic conditions, which mimic the native disc microenvironment, accelerate differentiation of hMSCs within the hydrogel system, towards the NP phenotype without the need for chondrogenic inducing medium or additional growth factors, thus simplifying the treatment strategy for the repair of IVD degeneration.